Risk factors of self-neglect among community living older persons in Selangor, Malaysia - Mardan, Homa (2016)
Older Malaysian recorded high prevalence of self-neglect compared to other types of elder abuse. The prevalence of elder self-neglect continues to rise due to population aging. This study aimed to develop an elder self-neglect instrument and identify predictors of self-neglect among community-dwelling older adults living at Selangor. In addition, this study also examines the mediating role of self-efficacy in the relationship between significant predictors on self-neglect. Self-care theory, selfefficacy theory and the biopsychosocial model form the theoretical background of this study. This was a cross-sectional study and the sampling of this study was assisted by the Department of Statistics Malaysia to randomly selected a representative sample from Selangor. Two hundred and one older persons were successfully interviewed in their homes by using structured questionnaires. A new instrument to measure the elder self-neglect (ESN) was developed from this study. The scale yielded four factors, namely, ‘changes in attitude,’ ‘personal behavior and environment,’ ‘personal health and hygiene’ and ‘lifestyle.’ The reliability of this instrument and sub-scales shows sufficient internal consistency, with Cronbach alphas between 0.90-0.76 respectively. Multiple linear regression results showed that older age, lower ADL, higher depressive symptoms, and lower self-efficacy were significantly predicted elder self-neglect. Self-efficacy fully mediated the association between the social network on ESN, partially mediated ADL and depression on ESN. This study provides a deeper understanding of the phenomenon of elder self-neglect among older adults living in Selangor. The newly developed instrument from this study could be used by researchers and social care workers to identify the selfneglect older adults. The findings of this study are useful for therapists, counselors, gerontologists, and policymakers to develop programs and policies to identify, prevent and report elder self-neglect cases in the community.